Mediating Customer Engagement Based on Content Marketing and Product Variety on Purchace Intention - Fauziah Nur Septiani; Popy Rufaidah (Dinasti Publisher, 2024)
This study investigated the role of content marketing and product variety on purchase decisions through customer engagement. The study was executed on the customers of local Indonesian footwear, namely Noosa Official, the MSME based in Bandung City. A total of 360 respondents were selected with the criteria of being 15 to 60 years old, living in Indonesia, and as followers of the Noosa Official Instagram for at least three months. The questionnaire contains 36 questions. The survey was self-administered and conducted online, and then the data obtained was analyzed using descriptive and SEM-PLS analysis. This study concluded that content marketing significantly and positively affects customer engagement and decisions. The indirect effect of content marketing on customer decisions mediated by customer engagement is also significant. Product variety only significantly affects customer decisions positively. Product variety has a positive but insignificant effect on customer engagement. Customer engagement is also negligible in mediating the influence of product variety on customer decisions. Lastly, customer engagement is also known to significantly influence customer decisions positively.